Association between mobile phone addiction, sleep disorder and the gut microbiota: a short-term prospective observational study - Zhu, Zhihui; Zhang, Jianghui; Yuan, Guojing; Jiang, Meng; Zhang, Xueqing; Zhang, Kexin; Lu, Xiaoyan; Guo, Haiyun; Yang, Huayu; Jin, Guifang; Shi, Haiyan; Du, Jun; et al. (Frontiers in Microbiology, 2023)
Bidirectional communication between the gut microbiota and the brain has sparked interest in exploring the link between mobile phone addiction (MPA) and sleep disorders (SD) in microbiome research. However, investigating the role of gut microbiota in this relationship using animal models presents challenges due to the unique nature of MPA, and human research in this area is scarce. We recruited 99 healthy college students to evaluate the gut microbiome using 16S rRNA gene amplicon sequencing and assess MPA and SD at baseline and after a two-month follow-up. Multiple covariate-adjusted statistical models, including linear regression, permutational multivariate analysis of variance and so on, were employed to determine microbiome associations with MPA at baseline and changes in SD at follow-up. Our findings revealed negative associations between MPA and three alpha diversity metrics, along with alterations in bacterial composition. MPA showed negative associations with the relative abundance of Bacteroidetes, while displaying positive associations with Actinobacteria and Bifidobacteriales. Conversely, Actinobacteria exhibited a negative association with increased SD. This study has established a significant link between MPA and a decrease in the alpha diversity of the gut microbiota. Actinobacteria was associated with MPA and SD, respectively. Additional investigation is needed to fully comprehend the relationship between comorbid behavioral disorders and the gut microbiota.